Modeling as sensemaking: towards a theory of modelling in physics education. (15th September 2021) - Sands, David
Abstract: Drawing on psychological evidence in problem solving and reasoning, a theory of modelling in physics is advanced. Modelling is framed as a process of making sense of the physical world. The sensemaking process is identified as having at least three distinct stages: making sense of the problem, making sure that the model makes sense, and finally, making sense of the physical world using the model. Key to first stage is the construction of a qualitative mental model. Evidence is cited from the psychological literature in favour of mental modelling as the primary mechanism by which humans reason. The second stage requires the qualitative ideas and relationships contained in the mental model be expressed mathematically so that the validity of the model can be tested in limiting cases and particular circumstances. The last stage involves testing the explanatory and predictive power of the model against known phenomena. The entire process is based on the creation of different representations and their consistent translation across the different stages of the modelling process. It is shown how these ideas can be incorporated into teaching and examples of teaching practices based on these ideas are given.